Factores sociales que influyen en la calidad de envejecimiento de los adultos mayores de dos instituciones públicas del distrito de Guadalupe, 2018-2021 - Uriol Castillo, Gaudy Teresa (2023)
The objective of this research was to analyze how social factors influence the quality of aging of older adults from CIAM-CAM District of Guadalupe for the period 2018-2021. It was a mixed investigation, which collects quantitative and qualitative data since it tries to analyze the unique experience of aging, it was a descriptive, non-experimental, correlational, cross-sectional investigation, establishing the influence of social factors on the way of aging. The techniques used were the interview, survey and observation and as instruments, the interview guide, observation guide and questionnaire applied to the total population of said institutions (130 older adults). The results of the study show that 35% of the older adults belonging to the two public institutions of the district of Guadalupe Senior Adult Center (CAM) and Comprehensive Senior Adult Center (CIAM), their ages range between 75-80 years, 45 % are widowed, requiring a support network with greater demand, they present greater male participation, likewise the results showed that in the pandemic period 28% never had material support from their family, a different situation was presented in the prepandemic period where 42 % of older adults always had the support of their primary network. This situation evidenced the contribution of the secondary network friends, neighbors who 48% gave material support. In the same way, emotional support in 34% was never perceived, in relation to informational support, 50% of older adults showed difficulty in accessing important information. Noting the importance of this study given that it recognizes the predominance of social factors and how, when they develop under normal conditions, they promote adequate aging, thus requiring their analysis, identification and strengthening.